Tanggung Jawab PT. POS Indonesia (Persero) Cabang Tabanan Terhadap Wanprestasi Pengiriman Barang - Ni Made Septyawati; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Post is a written communication service and electronic mail, package service, logistics service, financial transaction service, and post agency service for public purpose. Regulation regarding the post is regulation number 38 in 2009 and Government regulation number 15 in 2013. But in the service post often defaultsin shipping goods. The formulation of the problem to be discussed ishow is legal responsibility Tabanan Post Office for default on consumers because of damage and loss of consumer goods and how default settlement between damaged and lost consumer goods by Tabanan post office. In conducting this research is used empirical research type that is trough field research. To accountthe actions Tabanan post office give compensation to consumers corresponding wiith regulation number 38 in 2009 and refers to the decision of the board of directors number KD 128/DITRATKET/0616 regarding compensation for domestic letters and packages.Legal responsibility of Tabanan post office for default on consumers for damage and loss of consumer goodsis by way of out of court, this mothod is achieved by riconcile the parties with an agreement where the parties are harmed service users to request compensation to Tabanan post officeand negotiate about the amount of compensation.